2004
DOI: 10.1063/1.1770475
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-driven dewetting and rim instability

Abstract: An experimental method suitable for reproducible results has been used to investigate dewetting behavior of thin films of solvent-laden polymer. This solvent-driven dewetting enables one to change spreading coefficient by an order of magnitude that is not readily realizable in thermal dewetting and to study polar interactions that have not been fully exploited experimentally. While the film instability is similar to that found in thermal dewetting, the rim instability is quite different. Two different types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 38 publications
6
71
0
Order By: Relevance
“…14 was previously observed in the dewetting of polymer films 39,40) and in the Plateau-Rayleigh instability in polystyrene troids 41) .…”
Section: Discussionmentioning
confidence: 81%
“…14 was previously observed in the dewetting of polymer films 39,40) and in the Plateau-Rayleigh instability in polystyrene troids 41) .…”
Section: Discussionmentioning
confidence: 81%
“…44 In the present systems, for all samples, we found that S o 0 for each sample, in principle, a dewetting phenomenon occurred during the drying of the sophorolipids film. 99 In addition, Lee et al 100 have demonstrated that dispersive forces would stabilize the film while polar ones would induce dewetting. There were two dewetting processes that could happen: spinodal dewetting or heterogeneous nucleation.…”
Section: Discussionmentioning
confidence: 99%
“…For the further treatment it is necessary to consider the polymer solution film thickness l. This thickness established ex- perimentally as ∼1 µm is on one hand sufficiently large in order to neglect intermolecular forces, acting between the polymer solution and the substrate [12], and on the other hand it is sufficiently small to ignore the gravity. Indeed, the criterion l l c is fulfilled, where l c is the critical thickness introduced by de Gennes and given by [22]:…”
Section: Patterning Under Evaporation Of a Poor Solventmentioning
confidence: 99%
“…Dewetting of polymer solutions is accompanied with a variety of physical processes, which were studied extensively in both theoretical and experimental aspects [11,12]. The practical interest to the dewetting of polymer solutions was stipulated by the possibility to create micro-and nanometrically scaled structures.…”
Section: Introductionmentioning
confidence: 99%